Graphene Quantum Dots for Fluorescent Labeling of Gelatin‐Based Shear‐Thinning Hydrogels. Issue 7 (9th July 2021) - Nasrollahi, Fatemeh; Nazir, Farzana; Tavafoghi, Maryam; Hosseini, Vahid; Ali Darabi, Mohammad; Paramelle, David; Khademhosseini, Ali; Ahadian, Samad
Abstract : Injectable Biomaterials In article number 2000113, Ali Khademhosseini, Samad Ahadian, and co‐workers use biocompatible graphene quantum dots for imaging a physically crosslinked and injectable shear‐thinning biomaterial of gelatin hydrogel and silicate nanoplatelets. The biomaterial shows a robust and stable fluorescence signal in vitro and in animal models, suggesting a great potential in long‐term tracking and non‐invasive monitoring of the biomaterial in therapeutic applications.